Lendo e pensando com Ana Fani - Sandra Lencioni (Confins)
The Academic Trajectory of Ana Fani Alessandri Carlos was the title of a colloquium held to discuss her intellectual contribution, her academic life and her engagement in university life in all its fullness. Having followed her journey and having shared many experiences, it was decided that I should tell a little of this journey, precisely of an experience that we had together, which was that of having participated, for many years, in a discussion group known as the Martins Group. This group was multidisciplinary and gravitated for 18 years, from 1976 to 1993, around Professor José de Souza Martins, one of the greatest intellectuals in Brazil. They were years of intellectual formation outside the formal parameters of the University, reading and discussing two authors: Marx and Lefebvre. During the reading of Marx's works, we geographers of formation searched for new paths for Geography. Ana Fani and I also wanted to understand where we were in this crossroad of old and new paths, which made it essential to know the paths that had led us to this moment. Seeking the future and participating in a geography that was being renewed, we both went back to the past to understand where we were situated. And it was in this returning to the past and in the construction of the future that we walked together. Reading and thinking with Ana Fani is a bit of this story.